The night walk - Dorléans, Marie (Floris Books, 2020)
"Mama opened our bedroom door. 'Wake up, you two,' she whispered. 'Let's go, so we get there on time.' Excited, the sleepy family step outside into a beautiful summer night. The world is quiet and shadowy, filled with fresh smells and amazing sights. Is this what they miss when they're asleep? Together, they walk out of their sleeping village. What will they find in the dark landscape? This beautiful and evocative book movingly recalls family trips and the excitement of unknown adventure, while celebrating the awe-inspiring joy of the natural world."--Amazon.